Efficacy of botulinum-A for nocturnal bruxism pain and the occurrence of bruxism events: a meta-analysis and systematic review. Issue 2 (February 2022) - Cheng, Yutian; Yuan, Lingyu; Ma, Li; Pang, Fawei; Qu, Xinyu; Zhang, Aobo Albert
Abstract: The purpose of this study was to explore the treatment efficacy of botulinum-A (BTX-A) in nocturnal bruxism. Five electronic databases (PubMed, Web of Science, Cochrane, Embase and Clinical Trials) were searched to identify related randomised controlled trials up to September 1, 2020. Five evaluation indices were extracted, namely, the pain at rest and at chewing (PR and PC), the number of bruxism events (NBE) and the self-assessment by patients (SA), to assess the treatment efficacy of BTX-A in bruxism. All data analyses were conducted using Review Manager (Version 5.3; The Cochrane Collaboration, London, United Kingdom). Six studies were included in this review. The sample was composed of 148 participants. Compared with the placebo group, the BTX-A group showed the significantly improved the PR index scores (MD, 1.16 cm; 95%CI, 0.65 to 1.67 cm; p < 0.00001), slightly improved the PC index scores (SMD, 0.25; 95%CI -0.14 to 0.64; p = 0.21), and the NBEs were significantly decreased in the before-injection group compared with that in the after-injection group (MD, 1.72; 95%CI, 0.60 to 2.85; p = 0.003). The results of this study suggest that BTX-A possesses significant therapeutic efficiency for the relief of pain and events of bruxism. However, whether the events of bruxism would recur or rebound after botulinum toxin injection needs more follow-up clinical evidence.